1-(5-Bromo-2-oxoindolin-3-ylidene)thiosemicarbazone - Bandeira, Katlen C. T. (International Union of Crystallography, 2013)
The title molecule, C(9)H(7)BrN(4)OS, is essentially planar [r.m.s. deviation = 0.066 (2) Å], the maximum deviation from the mean plane through the non-H atoms being 0.190 (3) Å for the terminal amine N atom. In the crystal, molecules are linked through N—H⋯O and N—H⋯S interactions, generating infinite chains along the b-axis direction. In turn, the chains are stacked along the a axis via π–π interactions [centroid–centroid distance = 3.470 (2) Å] and further connected by N—H⋯Br interactions into a three-dimensional network. An intramolecular N—H⋯O hydrogen bond is also observed.